Related Questions

 Tags

Question by  Lisa45 (144)

# What is the answer to (9x-4)(3x+2)?

I have tried but can't get the right answer.

 +1 vote! +6 you voted Answer by  Clement (1453) To answer this question you need to make three steps. First, open the parenthesis: 9x*3x + (-4)*3x + 9x*2 + (-4)*2. Then, make basic calculations 27x^2 - 12x + 18x - 8. Finally, you need to simplify the expression a little bit more to obtain the final answer: 27x^2 + 6x - 8.

 +1 vote! +4 you voted Answer by  mamapuppy (241) You use FOIL to multiply the two factors, which means multiply the First, Outer, Inner, then Last parts of each factor together. First - 9x*3x=27x2 (the 2 means squared) Outer - 9x*2=18x Inner - -4*3x=-12x Last - -4*2=-8 Then combine to get 27x2+6x-8

 +1 vote! +4 you voted Answer by  Learner (350) 1) Multiply each term : 27x^2+18x-12x-8=0 27x^2+6x-8=0 2) 27x^2+6x-8=0 form of ax^2+bx+c=0 3) Using formula x=(-b+(SQRT(b^2-4ac)))/2a , x =(-b-(SQRT(b^2-4ac)))/2a and a=27,b=6,c=-8 we get x=4/9, x=-2/3

 +1 vote! +3 you voted Answer by  Yazuser (52) You just multiply the factors. (9x - 4)(3x + 2)= 27x(squared) + 18x - 12x -8. Simplifying: 27x(squared) + 6x - 8. When I write (squared) I mean that the x is multiplyid bi itself.